MANAGEMENT OF AIRSPACE CAPACITY AROUND UNCONTROLLED AERODROMES (Perner's Contacts, 2013)
This article focuses at heavy traffic at uncontrolled aerodromes, which is not dealt with and at the resulting critical situations of it and also with the appropriateness of implementing capacity management in aerodrome traffic zones to increase safety of General Aviation. This paper shows a model for this capacity management and solution for related issues.
Keywords: AFIS; AFIS Officer; ATZ; ADS-B; Workload